EFFECT OF ARNICA ON LENS REGENERATION IN ADULT FROG RANA CYANOPHLYCTIS - KHATRI, MANJU; JANGIR, O.P.; SHEKHAWAT, D.V.S.; ., PRAKASHACHARYA (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2005)
The present research aims at showing the role played by Arnica mont Q. in inducing lens regeneration even in the adult frog Rana cyanophlyctis which otherwise have lost this capacity. It has been observed that certain chemicals which increase the mitogenic activity and dedifferentiation may cause lens regeneration in amphibians. Arnica mont Q. was found to accelerate cell proliferation and dedifferentiation of pigmented epithelial cells (PECs) of dorsal iris and consequently induced the lens regeneration in adult frog. Arnica was found to induce lens regeneration in 80% adult frogs of treated group whereas lens regeneration was not reported even in a single animal of control group. Most of the regenerated lenses were small in size and modulated in shape. However, 40% regenerated lenses were found normal in size, shape transparency and histological features. The most common feature of Arnica mont Q. treated regenerates, was precocious differentiation of lenses, cytoplasmic vacuolization and hermiated lens fibers. It is speculated that this precocious differentiation caused by arnica, might be one of the reasons for smaller size of regenerated lenses.